THE IMPACT OF ALTERNATIVE ENERGY TO HUMAN SUSTAINABILITY: A REVIEW - ABDUL RAHMAN, FARAHIYAH; ABDUL RAHMAN, FAZILAH; A AZIZ, MD MANIRUZZAMAN; SAIDUR, R. (Human Sustainability Procedia, 2018)
The climate change and the depletion of fossil fuel is one of the world scale issue which will affect the human being. So, an innovative way must be addressed to solve these issues including environmentally friendly technologies to reduce air pollution, greenhouse effect, global warming, and climate change. In order of that, this paper present the innovative and sustainable way to mitigate these issues which are by using the alternative energy to substitute the fossil fuel usage. The objectives of this paper are: a) Define the sustainability and how the greenhouse gasesand fossil fuel depletion affect human being b) Address an innovative way to mitigate the issue c) Address the impact of alternative energy to environment, energy security, and economic. The alternatives energy discussed are included the utilization of CO2into fuel, and the implementation of biomass technology to produce biofuel. This is because these methods promoted positive impact when the CO2utilization can decrease its concentration in atmosphere and biofuel can enhance the socioeconomic. Moreover, both method can increase world energy security